Building bridges and deconstructing pathways in agriculture, nutrition and health. - Yates, Joe.; Manohar, Swetha.; Bhandari, Shiva.; Gersten, Zachary.; Kalamatianou, Sofia.; Saleh Arvin. (Tufts University. Tisch Library., 2018)
Abstract: Despite progress in evidence generation, however, there remain critical gaps in our understanding of the mechanisms through which agriculture and other nutrition-sensitive interventions can lead to improvements in diets and nutritional status at the population level; Keywords: Conference Report, Agriculture, Nutrition and health.; NIL publications.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy